MENGUSUNG CERITA TOPENG BETAWI TEMPO DOELOE MENUJU PERTUNJUKAN DUNIA - Siti Gomo Attas (Faculty of Humanities, Jember University, 2013)
This article elaborates the performance of Topeng Betawi story as a form of Betawi’s oral tradition presented at the Night of Old Jakarta Performance held at the VOC’s (Vereenigde Oost Indische Compagnie) Shipyard, Pluit Jakarta Utara, on Sunday, Desember 2, 2012. Foreign guests attending the show, invited by the head of North Jakarta municipality, came from 14 countries, including India, Japan, China, United States of America, Singapore, South Korea, and South Africa. The objective of this article is to report the aesthetical substance of the show in the context of world spectators. The article employs ethnographical method, interdiciplinary analysis, and performing arts approach. By doing so, it is expected that the article would be able to compose a writing that describe the performing of Topeng Betawi story during the 19th century in Batavia under the Dutch colonial rule. The aesthetic role of the stage was important as a media of performing Betawi’s folk story equipped with music, lighting, stage, and costums, which made the show more interesting. The producer with his expertise was able to organize the performance into a a garden party model before the VOC building. There were three things that made it interesting: (1) the great role of master ceremony in translating the story of Topeng Betawi (2) the shared exotic values of history as once being colonized, and (3 )the producer’s expertise in interestingly setting the show amazed the foreign spectators.Keywords: performance, folk story, Topeng Betawi, VOC era, exotic values